Quality evaluation method for electrode plate
By calculating the defect rate of the die-cut sample of the electrode plate and the shelving voltage test of the battery to be evaluated, the rapid and accurate evaluation of the quality of the electrode plate is achieved, and the problems of equipment dependence and cumbersome testing in the existing technology are solved, which is suitable for large-scale production Fast quality control in.
Patent Information
- Application Number
- CN202411370707.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-20
AI Technical Summary
The quality evaluation method of electrode pole sheets in the prior art requires a number of professional equipment, the test process is cumbersome, the cycle is long, and the cost is high, and it is not suitable for rapid quality control in large-scale production.
By dicing the electrode sheet into the electrode sheet sample, calculate the defect rate to judge the adhesion between the electrode coating and the current collector, and by testing the shelving voltage of the battery to be evaluated, the distribution uniformity of the electrode active material is determined, so as to achieve the electrode counteracting electrode Quick and accurate evaluation of the quality of the extreme sheet.
降低了对设备的要求,简化了测试步骤,缩短了测试时间,降低了成本,提高了测试效率,适合大规模生产中的快速质量控制,并且测试无损,结果更准确。
Smart Images

Figure CN119165017A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode pole piece quality detection, and in particular to a method for evaluating the quality of an electrode pole piece. Background Art
[0002] In the field of battery manufacturing technology, such as lithium-ion battery preparation technology, the quality of electrode plates directly affects the performance and life of the battery. It is generally believed that electrode plates with uniform particle dispersion and strong adhesion have better quality (performance), so the quality of electrode plates can be evaluated by testing the uniformity of particle dispersion and adhesion of electrode plates.
[0003] In the prior art, the particle dispersion uniformity of the electrode sheet can be tested with the help of a number of professional equipment such as a scanning electron microscope (SEM), and the adhesion of the electrode sheet can be reflected by testing the peeling force of the electrode sheet. Although the above method can accurately evaluate the quality of the electrode sheet, it needs to rely on a number of professional equipment, the testing process is cumbersome, the cycle is long, the operation is difficult, the production cost is high, and it is not conducive to rapid quality control in large-scale production. Summary of the invention
[0004] The present invention provides a quality evaluation method for an electrode plate, which can accurately evaluate the quality of the electrode plate, has low requirements for testing equipment, simple testing steps, short testing time, low operating difficulty, and low cost, and is suitable for rapid quality control in large-scale production.
[0005] The present invention provides a method for evaluating the quality of an electrode plate, wherein the electrode plate comprises an electrode current collector and an electrode coating located on the surface of the electrode current collector, wherein the electrode coating comprises an electrode active material, and the method for evaluating the quality of the electrode plate comprises the following steps: punching the electrode plate into M1 electrode plate samples, where M1 is an integer greater than 1; calculating a defect rate P1, wherein P1=M2 / M1, where M2 is the number of electrode plate samples with defects, wherein the defect comprises an area in the electrode plate sample where the surface of the electrode current collector is exposed due to the peeling of the electrode coating, and the electrode coating in the electrode plate corresponding to P1≤40% The adhesion between the electrode coating and the electrode current collector is better than the adhesion between the electrode coating and the electrode current collector in the electrode plate corresponding to P1>40%; select the electrode plate samples without the defect among the M1 electrode plate samples, and assemble the electrode plate samples into a battery to be evaluated; test the shelf voltage of the battery to be evaluated, calculate the relative standard deviation RSD of the measured multiple shelf voltages, and the distribution uniformity of the electrode active material in the electrode active material layer corresponding to RSD≤0.45% is better than the distribution uniformity of the electrode active material in the electrode active material layer corresponding to RSD>0.45%.
[0006] Optionally, the diameter of the pole piece sample is 12-16 mm; and / or, M1 is 8-20.
[0007] Optionally, the adhesion between the electrode coating in the electrode electrode sheet and the electrode current collector corresponding to P1≤40% is qualified, preferably P1<30%.
[0008] Optionally, the method comprises: selecting a plurality of electrode sheet samples that do not have the defect, assembling the electrode sheet samples into a battery to be evaluated, testing the shelf voltage of the battery to be evaluated, and judging the distribution uniformity of the electrode active material in the electrode coating according to the shelf voltage, which specifically comprises: selecting a plurality of electrode sheet samples that do not have the defect, assembling each of the electrode sheet samples that do not have the defect into a battery to be evaluated; testing the shelf voltage of each of the batteries to be evaluated, and calculating the relative standard deviation RSD of the measured plurality of shelf voltages, if RSD≤0.45%, it indicates that the distribution uniformity of the electrode active material in the electrode active material layer is qualified.
[0009] Optionally, the process of testing the shelf voltage of the battery to be evaluated includes: placing the battery to be evaluated at room temperature for 2 to 4 hours, then placing it at 45° C. to 70° C. for 1 hour to 3 hours, and then testing the shelf voltage of the battery to be evaluated.
[0010] Optionally, the battery to be evaluated is a button battery.
[0011] Optionally, the electrode sheet is a positive electrode sheet.
[0012] Optionally, the electrode active material includes a lithium-containing positive electrode active material, and the lithium-containing positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese iron phosphate.
[0013] Optionally, the electrode active material includes a sodium-containing positive electrode active material, and the positive electrode sodium-containing active material includes one or more of sodium manganate, sodium ferrite, sodium phosphate pyrophosphate, sodium iron phosphate, sodium iron pyrophosphate, and Prussian blue analogs.
[0014] Optionally, the electrode sheet is a negative electrode sheet.
[0015] The present invention provides a method for evaluating the quality of an electrode plate, which determines the adhesion between an electrode coating and an electrode current collector in the electrode plate by measuring the defect rate of a plate sample obtained after punching the electrode plate, and determines the distribution uniformity (uniform dispersion of particles) of an electrode active material in the electrode coating by testing the shelf voltage of a battery to be evaluated including the plate sample, thereby achieving rapid and accurate evaluation of the quality of the electrode plate; the method has low requirements for test equipment, simple test steps, short test time, low operation difficulty, and low cost, and is suitable for rapid quality control in large-scale production; and the above-mentioned evaluation method can be used to test the same electrode plate, and the test result is more accurate, belonging to a non-destructive test, and the tested electrode plate can be used for other battery performance tests. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The peeling force test curve of the electrode sheet in Examples 1-3;
[0017] Figure 2 This is a SEM test image of the electrode sheet coating after the film sheet resistance is tested in Examples 1 to 3;
[0018] Figure 3 This is a picture of the electrode sheet after rolling in Example 3. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0020] The embodiment of the present invention provides a method for evaluating the quality of an electrode sheet, wherein the electrode sheet includes an electrode current collector and an electrode coating located on the surface of the electrode current collector, wherein the electrode coating includes an electrode active material, and the method for evaluating the quality of the electrode sheet includes the following steps: punching the electrode sheet into M1 electrode sheet samples, where M1 is an integer greater than 1; calculating a defect rate P1, wherein P1=M2 / M1, where M2 is the number of defective electrode sheet samples, wherein the above-mentioned defect includes an area in the electrode sheet sample where the surface of the electrode current collector is exposed due to peeling of the electrode coating, and P1≤40% of the corresponding electrode sheet The adhesion between the electrode coating and the electrode current collector is better than the adhesion between the electrode coating and the electrode current collector in the electrode plate corresponding to P1>40%; select the electrode plate samples without the above defects among the above M1 electrode plate samples, and assemble the above electrode plate samples into a battery to be evaluated; test the shelf voltage of the battery to be evaluated, calculate the relative standard deviation RSD of the measured multiple shelf voltages, and the distribution uniformity of the electrode active material in the electrode active material layer corresponding to RSD≤0.45% is better than the distribution uniformity of the electrode active material in the electrode active material layer corresponding to RSD>0.45%.
[0021] According to the research and analysis of the inventors: In the embodiment of the present invention, the defect rate of the electrode sheet sample (punched sheet) after the electrode sheet is punched is used as an evaluation index to evaluate the peeling condition (material drop condition) of the electrode coating on the electrode sheet sample, which is used to judge the adhesion condition (adhesion quality) between the electrode coating and the electrode current collector in the electrode sheet. At the same time, the electrode sheet samples without the above defects are assembled into a battery to be evaluated, and the shelf voltage of the battery to be evaluated is used as an evaluation index to evaluate the potential consistency of the battery to be evaluated, which is used to judge the distribution uniformity of the electrode active material in the electrode coating (coating uniformity of the electrode active material or particle dispersion uniformity). In this way, The comprehensive evaluation of the quality of the same electrode plate is more accurate and comprehensive than the existing single evaluation technology, and can better reflect the actual condition of the electrode plate. Moreover, the above evaluation (test) process is a non-destructive test and does not damage the electrode plate. After testing the shelf voltage of the above-mentioned battery to be evaluated, other electrochemical performance tests can be carried out normally. In addition, the above evaluation method does not require the use of professional equipment such as scanning electron microscopes (SEM) and electrode peeling force testers. The test process is simplified, the test steps are simple, and the test time is short. The quality of multiple electrode plates can be quickly evaluated (assessed) in a short time, which significantly improves the test efficiency.
[0022] Illustratively, the M1 may be an integer of 8 to 20, for example, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.
[0023] In some embodiments, the pole piece sample is a round piece with a diameter of 12 to 16 mm. For example, the pole piece sample may have a diameter of 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, or a range consisting of any two of them.
[0024] In order to more comprehensively and accurately evaluate the quality of the electrode sheet (coated electrode sheet), the electrode sheet can be divided into multiple different areas, and then punched in the above multiple different areas to obtain M1 electrode sheet samples. It is understandable that the ranges of the above multiple different areas can be roughly the same, and the number of electrode sheet samples punched in the above different areas can also be roughly the same. For example, punching is performed at the head, middle, and tail of the electrode sheet, respectively, to obtain 4 to 6 (for example, 4, 5 or 6) electrode sheet samples.
[0025] Observe whether there are defects in the above-mentioned pole piece samples. The above-mentioned defects include the presence of areas in the pole piece samples where the surface of the electrode collector is exposed due to the peeling of the electrode coating, that is, the problem of foil leakage and material falling. The defect rate P1 is obtained by calculating the ratio of the number of pole piece samples M2 with the above-mentioned defects to the number of pole piece samples M1 obtained by punching, that is, P1 = M2 / M1.
[0026] The adhesion between the electrode coating and the electrode current collector in the electrode plate is determined based on the defect rate P1.
[0027] Specifically, if the above P1≤40%, for example, P1 is 0%, 10%, 20%, 30%, 40% or a range consisting of any two of them, it indicates that the adhesion between the electrode coating and the electrode current collector in the electrode plate is qualified, and the electrode plate can be used to make a battery cell. For example, if 18%≤P1≤40%, it indicates that the adhesion between the electrode coating and the electrode current collector in the electrode plate is qualified, that is, the electrode plate has qualified adhesion, and the electrode plate can be used to make a battery cell. If 0%≤P1≤18%, it indicates that the adhesion between the electrode coating and the electrode current collector in the electrode plate is good, that is, the electrode plate has good (strong) adhesion, and the electrode plate can be used to make a battery cell. In actual production, P1<30% can be used as a control standard for the quality of electrode plates.
[0028] If the above P1>40%, it indicates that the adhesion between the electrode coating in the electrode plate and the electrode current collector is poor, and there is a risk of peeling (dropping) of the electrode coating on the electrode plate when the electrode plate is used to make a battery cell.
[0029] Select the pole piece samples that do not have the above defects from the above M1 pole piece samples, and assemble these pole piece samples into batteries to be evaluated. Different materials (electrode active materials, conductive agents, binders, etc.) have different potential voltages. When the formula of the electrode coating is fixed, if the electrode active materials in the electrode coating of the electrode sheet are evenly distributed (evenly coated), the potential voltages at various locations of the electrode sheet should be the same (or the difference is not significant), and the voltage of the battery to be tested assembled from the electrode sheet samples that do not have the above defects in the same electrode sheet should also be the same. If the electrode active materials in the electrode coating of the electrode sheet are unevenly distributed (unevenly coated), the potential voltages at various locations of the electrode sheet will be different, and the voltage of the battery to be tested assembled from the electrode sheet samples that do not have the above defects in the same electrode sheet will also be different. Therefore, the shelf voltage of the battery to be tested can be tested to determine the uniformity of the distribution of the electrode active materials in the electrode coating (whether the coating is uniform) based on the above shelf voltage, that is, the uniformity of the distribution of all materials such as the electrode active materials, conductive agents, binders, etc. in the slurry of the electrode coating.
[0030] In some embodiments, the process of testing the shelf voltage of the battery to be evaluated includes: placing the battery to be evaluated at room temperature for 2 to 4 hours, for example, 2 hours, 3 hours, 4 hours or a range consisting of any two thereof, and then placing it at 45°C to 70°C (high temperature), for example, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or a range consisting of any two thereof, for 1 hour to 3 hours, for example, 1 hour, 2 hours, 3 hours or a range consisting of any two thereof, and then testing the shelf voltage of the battery to be evaluated.
[0031] Select the pole piece samples without the above defects from M1 pole piece samples, assemble these pole piece samples into a battery to be evaluated, test the shelf voltage of the battery to be evaluated, and judge the distribution uniformity of the electrode active material in the electrode coating according to the shelf voltage, specifically including: select multiple pole piece samples without defects, assemble each pole piece sample without defects into a battery to be evaluated; test the shelf voltage of each battery to be evaluated, and calculate the relative standard deviation RSD of the measured multiple shelf voltages. If RSD≤0.45%, it indicates that the distribution uniformity of the electrode active material in the electrode active material layer is qualified. It can accurately reflect the distribution uniformity of the electrode active materials of the electrode plate, and effectively solves the problem in the prior art that the resistivity of multiple sites of the electrode plate cannot be accurately reflected (feedback) The distribution uniformity of the electrode active materials (particle dispersion uniformity); if the above RSD>0.45%, it indicates that there are uneven areas in the distribution of the electrode active materials in the electrode active material layer, and there is agglomeration of the conductive agent or the positive electrode material, that is, the electrode active materials, conductive agents, binders and other materials in the slurry of the electrode coating are unevenly distributed.
[0032] During specific implementation, a conventional battery internal resistance tester may be used to test the shelf voltage of the battery to be evaluated.
[0033] After judging the adhesion and particle dispersion uniformity of the electrode sheets by testing the defect rate and shelf voltage of the electrode sheets, since the above-mentioned testing process is a non-destructive test, the internal resistance of the same electrode sheets can also be tested with accurate test results, thus avoiding problems such as electrode sheet damage and inaccurate resistance (resistivity) test results caused by destructive tests such as peel strength tests.
[0034] In addition, in actual battery systems, the internal resistance of the battery is not completely equivalent to the resistance (resistivity) of the electrode sheet. The internal resistance of the battery includes two parts: electron transmission (resistance) and ion migration. We cannot only consider the resistance (resistivity) of the electrode sheet and ignore the ion migration part. The electrode sheet after the lossy test cannot be used to assemble the battery because it has been damaged. Therefore, the internal resistance of the battery can only be represented by the resistance of the electrode sheet, but this is not the real internal resistance of the battery. The evaluation method of the embodiment of the present invention adopts non-destructive testing, and the electrode sheet after the test can be used to assemble the battery and test the internal resistance of the battery, thereby avoiding the above problems.
[0035] In some embodiments, the battery to be evaluated is a button battery.
[0036] It is understandable that the battery to be evaluated may include a positive electrode shell, a positive electrode plate, a separator, an electrolyte, a negative electrode plate, a gasket, a spring sheet, and a negative electrode shell.
[0037] The battery to be evaluated can be prepared by the following process: assembling a positive electrode shell (such as a conventional 304 stainless steel shell), a positive electrode sheet, a separator, an electrolyte, a negative electrode sheet, a gasket, a spring sheet, and a negative electrode shell (such as a conventional 304 stainless steel shell) into a battery to be evaluated according to conventional methods in the art.
[0038] In some embodiments, the electrode plate is a positive electrode plate. The positive electrode plate is selected from the electrode plate samples without the above defects among the M1 electrode plate samples.
[0039] In some embodiments, the electrode plate is a negative electrode plate. The negative electrode plate includes a negative electrode current collector and a negative electrode coating located on the surface of the negative electrode current collector, wherein the negative electrode coating includes a negative electrode active material, and the negative electrode active material may include one or more of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase microspheres, silicon-based composite materials, and lithium titanate.
[0040] The evaluation method of the embodiment of the present invention can be applied to the quality evaluation of electrode plates in lithium-ion batteries (systems) or sodium-ion batteries (systems).
[0041] When evaluating the quality of the positive electrode sheet in the lithium-ion battery, the electrode active material in the lithium-ion battery (battery to be evaluated) includes a lithium-containing positive electrode active material, and the above-mentioned lithium-containing positive electrode active material includes one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese iron phosphate. In addition, the negative electrode sheet in the lithium-ion battery can use a metal lithium sheet; the diaphragm can be selected from one of a polypropylene diaphragm (PP film), a polyethylene diaphragm (PE diaphragm), and a PP / PE composite film; the electrolyte may include an electrolyte lithium salt, a solvent, and an additive, wherein the electrolyte lithium salt may include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethylsulfonate, and lithium diacetate borate, the solvent may include at least two of ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate, and the additive may include one or more of vinylene carbonate, propylene carbonate, vinyl sulfate, 1,3-propane sultone, and lithium difluorophosphate.
[0042] When evaluating the quality of the positive electrode in the sodium ion battery, the electrode active material in the sodium ion battery (battery to be evaluated) includes a sodium-containing positive electrode active material, and the above-mentioned positive electrode sodium-containing active material includes one or more of sodium manganate, sodium ferrate, sodium ferric phosphate pyrophosphate, sodium ferric phosphate, sodium ferric pyrophosphate, and Prussian blue analogs. In addition, the negative electrode in the sodium ion battery can use a sodium metal electrode; the electrolyte may include an electrolyte sodium salt, a solvent, and an additive, wherein the electrolyte sodium salt includes one or more of sodium hexafluorophosphate, sodium perchlorate, and sodium fluorosulfonimide.
[0043] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0044] Example 1
[0045] This embodiment provides a quality evaluation method for a nickel-cobalt-manganese-lithium oxide positive electrode sheet, comprising:
[0046] Punch the head, middle and tail of the positive electrode sheet respectively to obtain 5 electrode sheet samples (small discs) with a diameter of 14 mm each, that is, a total of 15 electrode sheet samples with a diameter of 14 mm are obtained;
[0047] The 15 electrode samples were observed, and the number of electrode samples with defects (defects include areas in the electrode samples where the electrode current collector surface is exposed due to peeling of the electrode coating, i.e., foil leakage and material drop problems) was recorded as 3, and the defect rate P1 = 3 / 15 = 20% was calculated;
[0048] Select 9 electrode samples without the above defects from the above 15 electrode samples, and assemble them into 9 batteries to be evaluated (button batteries), wherein, in the 9 batteries to be evaluated, the positive electrode is the electrode sample without the above defects, the negative electrode is a metal lithium sheet, the diaphragm is a conventional PP diaphragm, and the electrolyte includes ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 3:4:3, as well as lithium hexafluorophosphate and vinylene carbonate, wherein in the electrolyte, the concentration of lithium hexafluorophosphate is 1 mol / L, and the mass percentage of vinylene carbonate is 1%; assemble the positive electrode shell (conventional 304 stainless steel shell), the positive electrode sheet, the diaphragm, the electrolyte, the negative electrode sheet, the gasket, the spring sheet, and the negative electrode shell (conventional 304 stainless steel shell) into a battery to be evaluated;
[0049] The battery to be evaluated was placed at room temperature for 2 hours and then at 60°C for 1 hour. The shelf voltage of the battery to be evaluated was then tested. The relative standard deviation of the multiple shelf voltages measured was calculated to be RSD = 0.41% (≤0.45%), indicating that the distribution of the electrode active material in the electrode active material layer was relatively uniform (relatively uniform).
[0050] The quality of the electrode plates of Examples 2 to 19 was evaluated with reference to the process of Example 1. The electrode plates, the number of plate samples M1 (the number of punched plates), the diameter of the plate samples, the number of defective plate samples M2 (the number of defective discs), the defect rate P1, the number of batteries to be evaluated, the conditions for testing the shelf voltage (the batteries to be evaluated were placed at room temperature for Ah, then placed at B℃ for Ch, and then the shelf voltage of the batteries to be evaluated was tested), the relative standard deviation RSD of the shelf voltage, etc. are summarized in Table 1.
[0051] Table 1
[0052]
[0053]
[0054] Test example
[0055] The nickel cobalt manganese oxide positive electrode sheet remaining after punching in Examples 1 to 19 was subjected to a peeling force test, and the test process included: sticking a certain width of transparent tape on the bottom of a clean steel ruler, sticking a double-sided tape on the transparent tape, sticking the remaining nickel cobalt manganese oxide positive electrode sheet on the double-sided tape, rolling it back and forth with a pressure roller for 3 times, folding the remaining unsticked section of the nickel cobalt manganese oxide positive electrode sheet 180 degrees, clamping it on a peeling force tester for testing, and reading the final peeling strength test result;
[0056] A four-probe sheet resistance meter was used to test the sheet resistance of the positive electrode coating remaining on the tape after peeling (six parallel tests were performed, and the relative standard deviation RSD was calculated); the positive electrode coating after the sheet resistance test was placed under a SEM (scanning electron microscope) to observe its fine morphology.
[0057] Test Results
[0058] Table 2 Defect rate and peeling force test data of electrode plates
[0059]
[0060] Data Analysis:
[0061] 1. The defect rate P1 of Example 1 is 20%, indicating that the adhesion between the electrode coating and the electrode current collector in the electrode plate is qualified, that is, the electrode plate has qualified adhesion, and the electrode plate can be used to make a battery cell; the defect rate P2 of Example 2 is 6.70%, indicating that the adhesion between the electrode coating and the electrode current collector in the electrode plate is good, that is, the electrode plate has good (strong) adhesion, and the electrode plate can be used to make a battery cell; the defect rate P2 of Example 3 is 46.70%, indicating that the adhesion between the electrode coating and the electrode current collector in the electrode plate is poor (weak), and there is a risk of peeling (dropping) of the electrode coating on the electrode plate when the electrode plate is used to make a battery cell (from Figure 3 It can also be seen that the electrode sheet of Example 3 has a material drop problem after rolling, which does not meet the actual production requirements of the battery cell;
[0062] 2. The defect rate P1 of the electrode sheets of each embodiment is consistent with the peeling strength test result of the electrode sheets. When P1 is between 18% and 40%, it indicates that the adhesion between the electrode coating in the electrode sheet and the electrode current collector is qualified, and the electrode sheet has qualified adhesion (peeling strength 0.2-1N / 20mm), and can be used to make battery cells; P1 is between 0% and 18%, indicating that the adhesion between the electrode coating in the electrode sheet and the electrode current collector is good, that is, the electrode sheet has strong adhesion (peeling strength>1N / 20mm); when P1>40%, it indicates that the adhesion between the electrode coating in the electrode sheet and the electrode current collector is poor (peeling strength<0.2N / 20mm). Figure 1 The peeling force test curve of the electrode plates in Examples 1-3 shows that the above peeling force test results are accurate and the test results are stable.
[0063] Table 3 Shelf voltage and relative standard deviation (RSD) of each battery (button cell) to be evaluated in each embodiment
[0064]
[0065]
[0066] Table 4 Film resistance and relative standard deviation (RSD) remaining on the tape after peeling in each embodiment
[0067]
[0068]
[0069] Data Analysis:
[0070] As can be seen from Table 3, the RSD of the shelf voltage in Example 1 is 0.41%, which indicates that the electrode coating material on the electrode plate of Example 1 is relatively uniformly dispersed (uniformity is qualified), and there is a slight conductive agent agglomeration phenomenon. The RSD of the shelf voltage in Example 2 is 0.2%, which indicates that the electrode coating material on the electrode plate of Example 2 is uniformly dispersed, and there is no conductive agent agglomeration phenomenon. The RSD of the shelf voltage in Example 3 is 0.77%, which indicates that there is obvious conductive agent agglomeration and positive electrode material agglomeration phenomenon in the electrode coating material on the electrode plate of Example 3.
[0071] It can be seen from Table 4 that the sheet resistance of the positive electrode coating remaining on the tape after peeling in Examples 1 to 3 fluctuates greatly, and the electrode coating particles on the electrode sheet are unevenly distributed. From the perspective of the RSD of the sheet resistance, the electrode coating particles on the electrode sheet of Example 3 are best dispersed;
[0072] Figure 2 The SEM test images of the electrode coating after the film resistance test in Examples 1 to 3 show that there is slight particle agglomeration in Example 1, the particles in Example 2 are evenly distributed, and there is serious particle agglomeration in Example 3, which is similar to the conclusion in Table 3 (i.e., the RSD of the shelf voltage) and seriously inconsistent with the results in Table 4 (film resistance and its RSD);
[0073] In summary, the resistivity test of the electrode sheet after stripping (the positive electrode coating left on the tape after stripping) is performed to see the uniform distribution of particles, and the result is inconsistent with the actual situation; because the electrode sheet is in a damaged state and the variable of tape is introduced, the fluctuation of the membrane resistance is large, and it is impossible to correctly judge whether the electrode sheet is evenly distributed. Although the test results of SEM are accurate, it depends on professional equipment, and the test cycle is long and the test process is cumbersome; the results in Table 3 (i.e., the RSD of the shelf voltage) are consistent with the actual results, the test method is simple and does not damage the electrode sheet, and the quality evaluation of the particle distribution and adhesion of the electrode sheet can be comprehensively carried out at the same time. In addition, the button cell (battery to be tested) after the test can be used for normal electrochemical testing;
[0074] By observing the electrode plates after rolling of Example 3, it can be seen that the lithium manganese iron phosphate positive electrode plates in Example 3 show obvious material falling off after rolling, which is consistent with the result that the peeling force of the electrode plates of Example 3 is relatively small, indicating that the evaluation result of the electrode plates of Example 3 (the electrode plates have poor adhesion and there is a risk of material falling off) by the evaluation method of the embodiment of the present invention is correct.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for evaluating the quality of an electrode sheet, characterized in that: The electrode plate comprises an electrode current collector and an electrode coating located on the surface of the electrode current collector, wherein the electrode coating comprises an electrode active material. The method for evaluating the quality of the electrode plate comprises the following steps: Punching the electrode sheet into M1 electrode sheet samples, where M1 is an integer greater than 1; Calculate the defect rate P1, where P1=M2 / M1, M2 is the number of defective electrode samples, the defect includes an area in the electrode sample where the surface of the electrode current collector is exposed due to the peeling of the electrode coating, and the adhesion between the electrode coating and the electrode current collector in the electrode electrode sheet corresponding to P1≤40% is better than the adhesion between the electrode coating and the electrode current collector in the electrode electrode sheet corresponding to P1>40%; Selecting pole piece samples without the defect from the M1 pole piece samples, and assembling the pole piece samples into a battery to be evaluated; The shelf voltage of the battery to be evaluated is tested, and the relative standard deviation (RSD) of the measured multiple shelf voltages is calculated. The distribution uniformity of the electrode active material in the electrode active material layer corresponding to RSD≤0.45% is better than the distribution uniformity of the electrode active material in the electrode active material layer corresponding to RSD>0.45%.
2. The method for evaluating the quality of an electrode sheet according to claim 1, characterized in that: The diameter of the pole piece sample is 12-16 mm; And / or, the M1 is 8-20.
3. The method for evaluating the quality of an electrode sheet according to claim 1, characterized in that: When P1≤40%, the adhesion between the electrode coating in the electrode plate and the electrode current collector is qualified, and preferably P1<30%.
4. The method for evaluating the quality of an electrode sheet according to any one of claims 1 to 3, characterized in that: The step of selecting a pole piece sample that does not have the defect from the M1 pole piece samples, assembling the pole piece samples into a battery to be evaluated, testing the shelf voltage of the battery to be evaluated, and judging the distribution uniformity of the electrode active material in the electrode coating according to the shelf voltage specifically includes: Selecting a plurality of electrode samples that do not have the defects, and assembling each of the electrode samples that do not have the defects into a battery to be evaluated; The shelf voltage of each battery to be evaluated is tested, and the relative standard deviation (RSD) of the measured shelf voltages is calculated. If RSD is ≤ 0.45%, it indicates that the distribution uniformity of the electrode active material in the electrode active material layer is qualified.
5. The method for evaluating the quality of an electrode sheet according to claim 4, characterized in that: The process of testing the shelf voltage of the battery to be evaluated includes: placing the battery to be evaluated at room temperature for 2 to 4 hours, then placing it at 45° C. to 70° C. for 1 hour to 3 hours, and then testing the shelf voltage of the battery to be evaluated.
6. The method for evaluating the quality of an electrode sheet according to any one of claims 1 to 4, characterized in that: The battery to be tested is a button battery.
7. The method for evaluating the quality of an electrode sheet according to any one of claims 1 to 4, characterized in that: The electrode sheet is a positive electrode sheet.
8. The method for evaluating the quality of an electrode sheet according to claim 7, characterized in that: The electrode active material includes a lithium-containing positive electrode active material, and the lithium-containing positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese iron phosphate.
9. The method for evaluating the quality of an electrode sheet according to claim 7, characterized in that: The electrode active material includes a sodium-containing positive electrode active material, and the positive electrode sodium-containing active material includes one or more of sodium manganate, sodium ferrite, sodium phosphate pyrophosphate iron, sodium iron phosphate, sodium pyrophosphate iron, and Prussian blue analogs.
10. The method for evaluating the quality of an electrode sheet according to any one of claims 1 to 4, characterized in that: The electrode sheet is a negative electrode sheet.
